IMPLEMENTASI PROGRAM BANTUAN SISWA MISKIN BAGI SISWA SMA NEGERI DI KOTA BINJAI - Sinulingga, Rosina (PERSPEKTIF, 2015)
This study will examine the implementation of programs concerning assistance to poor students for high school students in the city of Binjai State. As a form of implementation of programs aimed at improving human resources nation's children, especially in the city of Binjai . In connection with these two problems, namely how the proposed implementation of the assistance program for the poor students of SMA students in the city of Binjai and what are the constraints in the implementation of aid programs for the poor students of SMA students in the city of Binjai. To address these problems the proposed research literature and field research conducted in Binjai City Department of Education / Further data collected and analyzed by descriptive analysis. The results of the research and discussion to explain poor scholarship program ( BSM - state high schools ) in the city of Binjai is a program providing financial assistance to poor students to have access to education, the funds from the state budget. The purpose of this program is to increase the participation of poor people in Indonesia to gain access to education.